Allometric growth of non-carcass components in crossed lambs - Garcia, Iraides Ferreira Furusho; Alvarenga, Tharcilla Isabella Rodrigues Costa; Perez, Juan Ramon Olalquiaga; Almeida, Amelia Katiane de [UNESP]; Gallo, Sarita Bonagurio; Pereira, Idalmo Garcia; Alves, Nadja Gomes; Alvarenga, Flávio Augusto Pereira (Universidade Federal de Santa Maria, 2014)
Males and females, including purebred Santa Inês lamb (SI) and crosses between Santa Inês dams and Texel (TxSI), Ile de France (IFxSI) and Bergamasca (BxSI) sires were feedlot finished and slaughtered at 15, 25, 35 and 45kg live weight. After slaughter, the following non- carcass components were weighed and calculated the allometric growth. Lungs of BxSI males grew faster than those of SI and TxSI. Trachea/esophagus in SI and TxSI males grew slower than IFxSI and BxSI. Kidneys BxSI males grew faster than TxSI and IFxSI. Livers of female TxSI lamb grew more rapidly than those of females in the other genetic groups. In both males and females, the rumen/reticulum grew faster in the TxSI group than SI and BxSI groups.

Machos e fêmeas, Santa Inês puros (SI) e cruzados de matrizes Santa Inês com reprodutores das raças Texel (TxSI), Ile de France (IFxSI) e Bergamácia (BxSI), terminados em confinamento e abatidos aos 15, 25, 35 e 45kg de peso vivo. Após o abate, foram tomados os pesos das vísceras e analisado o crescimento alométrico. O pulmão dos machos BxSI cresceu em taxas mais elevadas que SI e TxSI. A tráqueia/esôfago dos machos SI e TxSI cresceu mais lentamente que dos IFxSI e BxSI. Os rins dos machos BxSI cresceram mais rápido comparado aos dos TxSI e IFxSI. O fígado das fêmeas TxSI cresceu em taxas mais elevadas quando comparadas às fêmeas dos outros grupos genéticos. Os machos e fêmeas do grupo TxSI apresentaram taxas de crescimento maiores para rúmen/retículo, respectivamente, comparado aos grupos SI e BxSI.
Crescimento alométrico dos não componentes da carcaça de cordeiros cruzados
Keywords: alometria; crescimento; desenvolvimento corporal; cruzamento; ovinos; allometry; growth; crossbreed; body development; sheep